.Development Strategy Of Bayung Gede Ethnıc Tourısm Vıllage To Increase Tourıst Vısıts In Banglı Regency, Balı - Ni Kadek Suartini; Ni Ketut Arismayanti; Nyoman Ariana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Bayung Gede Ethnic Tourism Village, located in Kintamani, Bangli Bali, has a unique tradition and culture labeled Tourism Village. However, his visits are still fluctuating downhill. This study aims to develop a strategy for developing Bayung Gede Ethnic Tourism Village as one of the ethnic villages to increase the number of tourists visiting. This research uses a qualitative approach and is complemented by quantitative data collection by observation methods, interviews, literature studies, and research questionnaires. This study used IFE, EFE, IE, SWOT, and QSPM matrix analysis. The SWOT analysis results obtained 8 alternative strategies for the development of Bayung Gede Ethnic Tourism Village. These alternative strategies are then analyzed using the QSPM matrix to determine the priorities of strategies that can be applied. There are 8 strategies selected, 1 of which is a priority to be implemented, namely improving the quality of human resources by conducting tourism training for the community on the development of maintaining villages. Based on the most significant TAS score, which is 7,382, It is continued with the determination of strategies obtained and selected based on periods, namely short-term, medium-term, and long-term, for the development of Bayung Gede Village to become a tourist village with many tourist visits.